B1-mobilstor: Materials for sustainable energy storage techniques - Lithium containing compounds for hydrogen and electrochemical energy storage - Bö Hme, B.; Minella, C.; Thoss, F.; Lindemann, I.; Rosenburg, M.; Pistidda, C.; Moller, Kasper; Jensen, T.; Giebeler, L.; Baitinger, M.; Gutfleisch, O.; Ehrenberg, H.; et al. (2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. New material concepts for hydrogen storage and lithium ion batteries are investigated in the joint ECEMP project B1 - Mobilstor. Chemical composition are essential for the performance of a storage material. A certain state of material can be effectively analyzed by in situ methods to obtain a maximum of information. For hydrogen storage the LiNH2MgH2system and as lithium ion batteryanode the Ge(cF136) allotrop are highlighted under this issue.